Prevalence of cognitive impairment and its related factors among Chinese older adults: an analysis based on the 2018 CHARLS data - Xueqin Wu; Xueqin Wu; Yufu Tang; Yushan He; Qiwei Wang; Qiwei Wang; Yinhui Wang; Xiujun Qin (Frontiers in Public Health)
BackgroundCognitive impairment is a major public health concern in aging societies. This study aimed to investigate the prevalence of cognitive impairment and its associated factors among Chinese adults aged 60 years and older using data from the 2018 China Health and Retirement Longitudinal Study (CHARLS).MethodsUtilizing data from the 2018 wave of CHARLS, we assessed participants’ cognitive status using the Mini-Mental State Examination (MMSE), and the influencing factors related to cognitive impairment were analyzed by using the chi-square test and multifactor logistic regression. The prevalence of cognitive impairment was stratified by gender, education level, residence, marital status, daytime napping, and nighttime sleep duration, and the trend of cognitive impairment prevalence with age was observed.Results9,804 participants were finally included in the study and the overall prevalence of cognitive impairment was 44.04% (95%CI, 43.02–45.06%). The prevalence was significantly higher in females (50.8%) than males (37.1%), and increased with age, from 41.5% in those aged 60–64 years to 57.7% in those aged ≥75 years. Lower educational level, rural residence, and being divorced/ widowed/unmarried were associated with a higher prevalence of cognitive impairment (all p < 0.001). Multifactor logistic regression indicated that older age (OR = 1.51, 95%CI, 1.33–1.73 for ≥75 vs. 60–64 years), female gender (OR = 1.54, 95%CI, 1.35–1.77), higher education (OR = 0.46, 95%CI, 0.42–0.51 for primary school and below vs. illiteracy), rural areas (OR = 2.35, 95%CI, 2.07–2.65 for village vs. the center of city/town), divorced/ widowed/unmarried status (OR = 1.40, 95%CI, 1.25–1.57) and participation in physical activity (OR = 0.80, 95%CI, 0.73–0.87) were significantly associated with cognitive impairment.ConclusionCognitive impairment is highly prevalent among older adults in China with substantial demographic disparities. Targeted interventions and public health strategies are needed to promote cognitive health in this rapidly aging population.